Seropositivity of hepatitis viral markers in icteric children - Sarker, Nihar Ranjan; Saha, Santosh Kumar; Ghosh, Dilip Kumar; Adhikary, Alpana; Mridha, Alamin; Alam, Md Razibul (Bangladesh Medical Journal, 2014)
Viral hepatitis is a major public health problem in the world affecting millions of children every year despite the availability of vaccines, prophylactic measures and improved sanitation. The prevalence of infection varies from country to country and within countries, having a close association with behavioral, environmental, host factors. This study was an attempt to evaluate the sero-prevalence rate of various viral hepatitis markers of 50 icteric children who attended pediatric outpatient department of Shaheed Suhrawardy Medical College Hospital from January 2010 to December 2010. All the patients were screened for HAV, HEV, HBV, HCV. Anti HAV IgM were positive in in 65.22 %, Anti HEV IgM in 34.78 % and HBsAg in 4% of icteric children. None of the icteric children were positive for hepatitis C virus. Most of the icteric children presented with fever, anorexia and nausea /vomiting. This study shows high rate of HAV and HEV infection among icteric children DOI: http://dx.doi.org/10.3329/bmj.v43i1.21373 Bangladesh Med J. 2014 January; 43 (1): 26-29